Illumination on Chemical Compounds from Qufeng Zhitong Capsule and Its Potential Pharmacological Mechanism against Rheumatoid Arthritis Based on UHPLC/Q-Orbitrap-MS Combined with Network Pharmacology Analysis. (7th December 2022) - Xue, Mengjie; Zhang, Lihua; Zhao, Yuting; Mu, Qixuan; Cui, Ying; Qian, Ke; Chai, Xin
Abstract : Qufeng Zhitong capsule (QZC), a Chinese patent medicine officially approved in China for the treatment of rheumatoid arthritis (RA) and other diseases, possesses the primary effects of dispelling wind, relieving pain, and promoting blood circulation, whose clinical applications have been confined owing to the incomplete elucidation of its chemical compositions and the underlying molecular mechanism for the treatment of RA. In this study, 61 compounds including 16 phenylpropanoids, 15 organic acids, 13 alkaloids, seven flavonoids, six iridoids, one saccharide, two aldehydes, and one saponin in QZC were simultaneously identified and traced to their herbal origins by ultra-high performance liquid chromatography tandem Q-Exactive Orbitrap high-resolution mass spectrometry (UHPLC/Q-Orbitrap-MS), where 31 of them were unambiguously identified by reference compounds, and the other 30 were tentatively characterized. Besides, all these compounds were proven to have potential pharmacological activity in the treatment of RA based on network pharmacology analysis. In conclusion, this study first investigated the chemical composition and potential pharmacological effects of the main chemical compounds in QZC, which will contribute to the revelation of bioactive compounds in QZC and provide evidence for clinical application.